Implementasi Mu’āmalah Māliyah Mazhab Yayasan Nurul Hayat - Imron Mustofa (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
Indonesia with majority Islam as its majority religion, with their obligation to give zakat, donations and alms, needs role model. The Nurul Hayat Foundation with all its business units is one of the institutions in mu'āmalah māliyah which should be considered as the role model. This article is field research. The results of this study indicate that the Nurul Hayat Foundation is implementing what they call the four commitments (independent, trustworthy, professional (ISO 9001: 2015), and implementing the 5R culture (mandiri/concise, amanah/neat, resik/clean, rawat/caring and rajin/diligent), and empowering). In institutional governance, Nurul Hayat applies four stages: the planning, organizing, implementing and supervising.